Pre-ramadan education and blood glucose monitoring as a safe ramadan fasting strategy for people with type 2 diabetes mellitus - Larasati, Meirina Dwi; Muninggar, Dian Luthfita Prasetya; Jaelani, Mohammad (Journal of Community Empowerment for Health, 2026)
Introduction: People with type 2 diabetes mellitus (T2DM) who choose to fast during Ramadan are at increased risk of metabolic complications, particularly hypoglycemia and hyperglycemia. Ensuring comfort and a sense of safety is essential to minimize these risks. Pre-Ramadan education focusing on dietary management and regular health monitoring may support safer fasting practices. This activity aimed to assess the impact of pre-Ramadan education on glycemic control and fasting safety among individuals with T2DM.Methods: This community service activity was conducted among individuals with T2DM participating in the Prolanis program at Tlogosari Wetan Primary Health Center, Semarang City. Educational sessions on dietary management during Ramadan fasting were delivered using PowerPoint presentations, and booklets were distributed to 46 participants. Health monitoring was subsequently conducted through home visits during Ramadan to assess complaints and the risk of glycemic disturbances, including blood glucose measurements, in 27 participants.Results: Pre-Ramadan education was implemented during Prolanis activities in February and March 2024, followed by health monitoring throughout Ramadan. Reported symptoms suggestive of hypoglycemia included sweating, chills, tremors, headaches, and hunger, while symptoms related to hyperglycemia included polyuria, dehydration, nausea, vomiting, and fatigue. Blood glucose monitoring performed two hours before breaking the fast showed values ranging from 73 mg/dL to 235 mg/dL. Approximately 25% of participants achieved controlled blood glucose levels during Ramadan fasting. Comparison of pre- and post-Ramadan fasting blood glucose measurements indicated a tendency toward improved glycemic control during Ramadan.Conclusion: Pre-Ramadan education programs can help glycaemic control and monitor the risk of complications in people with T2DM who fast during Ramadan.